Impacto do Reconhecimento de Ativos Fiscais Diferidos na Estrutura Financeira e no Desempenho Econômico de Empresas Brasileiras - Clóvis Antônio Kronbauer (Revista Contemporânea de Contabilidade, 2012)
The article aims is to analyze the impact of the deferred tax assets (DFAs) recognition in financial structure and economic performance of 36 companies that are part of new market level of corporate governance the BM&FBOVESPA, with data from financial statements for the period 2006 to 2008. The study approach is quantitative, and, related to the aims, descriptive; data was collected through documental analysis. It was found through the "t" test, that the recognition of DFAs has statistically significant impact on liquidity ratios and debt; and, .was applied the correlation test and dependency analysis through multiple regressions. The results reveal no significant relationship between the level of recognition of DFAs and explanatory variables.